2018
DOI: 10.22454/fammed.2018.217704
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Resident Perspectives on Curricula in Herbal Medicine

Abstract: Residents perceived a lack of adequate medical education on the use of herbal and dietary supplements. Results showed a brief workshop increased resident intentions to discuss supplement use with patients. Further education on supplement use may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
(37 reference statements)
0
2
0
Order By: Relevance
“… 101 Herbal medicine education for conventional medicine clinicians and pharmacists are found to be effective in promoting their confidence in communicating with patients about the use of herbal medicines and supplements. 102 , 103 Effective curriculum can be adapted and promoted in Universities across Western Pacific Region.…”
Section: Discussionmentioning
confidence: 99%
“… 101 Herbal medicine education for conventional medicine clinicians and pharmacists are found to be effective in promoting their confidence in communicating with patients about the use of herbal medicines and supplements. 102 , 103 Effective curriculum can be adapted and promoted in Universities across Western Pacific Region.…”
Section: Discussionmentioning
confidence: 99%
“…Foster et al assessed the perceived adequacy of the education received on DS among 65 family medicine residents from six Colorado programs. 27 The investigators reported that approximately 90% of the participants thought that they should have received more education and that only 48% received required education on supplements at all. Thus, it appears that greater efforts need to be directed toward preparing HCPs who are knowledgeable about CAM and confident in their abilities to provide proactive input and address questions about DS.…”
Section: Discussionmentioning
confidence: 99%